The Influence of EGCG on the Pharmacokinetics and Pharmacodynamics of Bisoprolol and a New Method for Simultaneous Determination of EGCG and Bisoprolol in Rat Plasma - Zeng, Weiwei; Lao, Sixian; Guo, Yi; Wu, Yufeng; Huang, Min; Tomlinson, Brian; Zhong, Guoping (Frontiers in Nutrition, 2022)
Background and Aim: Research has shown that green tea catechins may influence the activity of drug metabolizing enzymes and drug transporters. We examined whether epigallocatechin-3-gallate (EGCG) affected the pharmacokinetics and pharmacodynamics of bisoprolol in rats. Methods: A sensitive, specific liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was established for the quantitative determination of EGCG and bisoprolol. The pharmacokinetic parameters of EGCG and bisoprolol in Sprague-Dawley (SD) rats were analyzed using non-compartmental methods with the aid of the computer program WinNolin. Blood pressure (BP) of spontaneously hypertensive rats (SHRs) was monitored by the tail-cuff method. Bisoprolol was given as single doses of 10 mg/kg with or without EGCG 100 mg/kg by gavage or by intravenous injection. Results: Intake of EGCG with bisoprolol by gavage significantly reduced the Cmax (mean Cmax from 2012.31 ng/mL to 942.26 ng/mL, P<0.05) and increased the Tmax (mean Tmax from 0.5 h to 0.83 h, P<0.01) for bisoprolol. After intravenous injection, EGCG significantly increased the apparent volume of distribution of bisoprolol (mean Vz/F from 1629.62 mL/Kg to 2473.27 mL/Kg, P<0.05) and tended to increase the clearance. The absolute bioavailability of bisoprolol was reduced from 92.04% to 66.05% in rats when bisoprolol was administered with EGCG. Heart rate reduction was less in SHRs when EGCG was given by gavage with bisoprolol whereas BP reduction occurred more rapidly. Conclusion: This study showed that the simultaneous administration of EGCG by gavage at a dose of 100 mg/kg was associated with decreased Cmax and increased Tmax of bisoprolol, and the Vz/F of bisoprolol was increased when administered with EGCG by intravenous injection in SD rats. Moreover, the early heart rate reduction with bisoprolol was attenuated and BP reduction occurred earlier when EGCG was given with bisoprolol by gavage in SHRs.